TECHNICAL EFFICIENCY OF PUBLIC SECTOR BANKS IN INDIA BY USING DATA ENVELOPMENT ANALYSIS - K. , Pushpanjali; K. , Muthyalappa (International Journal of Psychosocial Rehabilitation, 2018)
This study evaluates the efficiency of public sector banks in India using Data Envelopment Analysis (DEA). DEA is a non-parametric method used to assess the relative efficiency of decision-making units (DMUs) such as banks, by comparing the inputs and outputs. The analysis covers various aspects of banking operations, including financial performance, operational efficiency, and service quality, to identify the most efficient banks and provide insights for improving the performance of less efficient ones.